Habitat associations of woody plant species in evergreen–deciduous broadleaf karst forests in southwest China - Su, Liang; Du, Hu; Zeng, Fuping; Wang, Hua; Lu, Menzhen; Luo, Liujuan; Peng, Wanxia; Song, Tongqing (Frontiers in Ecology and Evolution, 2023)
The effects of habitat filtering on community assembly have been extensively researched, and topography has been identified as a critical factor influencing the spatial distribution of trees. In this study, a 25-ha plot was established in karst evergreen–deciduous broadleaf forests in southwestern China. Eight topographical factors were used to divide plots into four habitat types, i.e., hilltop, steep slope, gentle slope, and depression, using a multivariate regression tree. A total of 85 evergreen and deciduous tree species were recorded in these four habitats and classified into three life stages, the differentiation of which was assessed using torus-translation tests. A total of 65 species significantly positively associated with at least one habitat and 79 species significantly negatively associated with at least one habitat were identified. Most species, whether evergreen or deciduous, exhibited a positive correlation with steep slopes, whereas relatively few species were adapted to depressions. Moreover, the percentage of evergreen species positively associated with hilltops and steep slopes was higher than that of deciduous species. Both evergreen and deciduous species showed an increasing percentage of positive correlation with hilltops from the sapling stage to the mature stage. However, more evergreen species grew on steep slopes in the sapling stage, whereas deciduous species grew in the mature stage. Canonical correspondence was used to analyze the relationship between species and the eight topographical factors. Regardless of life form or life stage, results showed that species distribution was significantly affected by topography. Furthermore, the distribution of evergreen species on sapling-stage trees was found to be more influenced by topography, whereas deciduous species were more influenced by topography in the mature stage. Finally, elevation was identified as the most crucial topographical factor affecting species distribution.